Revealing, transforming, and display in Egyptian hieroglyphs - Klotz, David; Stauder, Andréas 1977- (De Gruyter, 2020)
This is the first synthesis on Egyptian enigmatic writing (also referred to as "cryptography") in the New Kingdom (c.1550–1070 BCE). Enigmatic writing is an extended practice of Egyptian hieroglyphic writing, set against immediate decoding and towards revealing additional levels of meaning. This first volume consists of studies by the main specialists in the field. The second volume is a lexicon of all attested enigmatic signs and values
Aus dem "Preface": "... origin in a workshop held in Basel on 23-24 May 2015 ..."
Keywords: Geschichte 1550 v. Chr.-1070 v. Chr.; Egyptian writing; Enigmatic writing; Enigmatik; Hieroglyphen; Kryptographie; cryptography; hieroglyphs; HISTORY / Ancient / Egypt; Kryptologie; Ägypten -- Altertum; Konferenzschrift -- 23.05.2015-24.05.2015 -- Basel